Detecting motorcycles in road scenes: differences between car drivers and motorcyclists - Khashawi, Fadhel (2011)
Many motorcycle “right of way” violations are believed to be a result of low conspicuity and a failure to perceive the motorcycle. Drivers with previous experience of riding motorcycles tend not to commit this type of violation, indicating an influence of awareness or expectancy. This thesis investigates the way these drivers with motorcycle experience inspect traffic scenes in the appearance of a motorcycle, and compares their performances to drivers with no motorcycle experience. It investigates also the effect of motorcycle awareness promotion signs such as “Think Bike” that are used in safety campaigns across the United Kingdom. It also tries to develop a design that could be used in eye movement studies to compare eye movements patterns of drivers with motorcycle experience and those who do not have motorcycle experience.